Repetitive generation of X-band superradiation at 3-GW peak power; IEEE International Conference on Plasma Science (ICOPS) - Yalandin M. I. Michael Ivanovich; Luybutin S. K.; Rukin S. N. Sergey Nikolaevich; Sharypov K. A. Konstantin Anatolyevich; Shpak V. G. Valery Grigoryevich; Shunailov S. A. Sergei Afanasievich; Slovikovsky B. G.; Timoshenkov S. P.; Ulmasculov M. R. Marat Rakhmetovich; Rostov V. V. Vladislav Vladimirovich; Grishin D. M.; Gubanov V. P. Vladimir Petrovich; et al. (2007, 2007)
Title screen